Assessment of The Impact of Online Learning Platforms on Academic Motivation - Pooja Jain; Sneha (Recent Trends in Social Studies, 2026)
Since the COVID-19 pandemic, online learning platforms have become an integral component of higher education systems worldwide. Digital platforms such as Google Classroom, Zoom, Moodle, and Microsoft Teams have transformed the way students access educational content and interact with instructors. While these platforms offer advantages such as flexibility, accessibility, and diverse multimedia resources, their influence on students’ academic motivation remains a critical concern. The present study aims to assess the impact of online learning platforms on academic motivation among students studying in selected colleges of Greater Noida. A descriptive cross-sectional research design was adopted, and data were collected using a structured questionnaire that measured various dimensions of academic motivation, including interest in learning, engagement, self-discipline, and goal orientation. The findings indicate that online learning platforms have a mixed impact on academic motivation. Positive outcomes include enhanced self-paced learning, improved access to educational resources, and increased autonomy in learning. However, challenges such as poor internet connectivity, technical difficulties, limited peer interaction, prolonged screen time, and feelings of isolation negatively affect students’ motivation levels. The study further highlights that teacher presence, interactive teaching strategies, timely feedback, and effective use of multimedia tools significantly enhance students’ academic motivation in online environments. The results emphasize the need for well-designed online instructional strategies, strong technological support, and active teacher–student interaction to promote sustained academic motivation. The study provides valuable insights for educators and institutions to improve the effectiveness of online learning platforms and foster motivated, engaged learners in digital education settings.
Keywords: Academic Motivation; Digital Education; Online Learning Platforms; Self-Regulated Learning; higher education; student engagement